Mapping Interactions between p27 and RhoA that Stimulate Cell Migration. Issue 6 (16th March 2018) - Phillips, Aaron H.; Ou, Li; Gay, Alexandre; Besson, Arnaud; Kriwacki, Richard W.
Abstract: p27 mediates cell cycle arrest by binding to and inhibiting cyclin-dependent kinase/cyclin complexes, but p27 can also contribute to pro-oncogenic signaling upon mislocalization to the cytoplasm. Cytoplasmic p27 stimulates cell migration by associating with RhoA and interfering with the exchange of GDP from RhoA stimulated by guanine nucleotide exchange factors. We used biophysical methods to show that the N-terminus of p27 directly interacts with RhoA in vitro . The affinity of p27 for RhoA is low, with an equilibrium dissociation constant of hundreds of micromolar; however, at high concentrations, p27 interfered with guanine nucleotide exchange factor-mediated nucleotide exchange from RhoA. We also show that promotion of cell migration in scratch wound cell healing assays requires full-length p27 despite the C-terminus being dispensable for the direct interaction between p27 and RhoA in vitro . These results suggest that there may be an unidentified factor(s) that associates with the C-terminus of p27 to enhance its interactions with RhoA and promote cell migration. Graphical abstract: Highlights: It is known that cytoplasmic mislocalization of p27 stimulates migration through RhoA. An N-terminal region of p27 binds RhoA and interferes with GDP exchange from RhoA. However, only full-length p27 can stimulate migration in cells.